A Quad‐Unit Dielectric Elastomer Actuator for Programmable Two‐Dimensional Trajectories - Chongjing Cao; Chuang Wu; Xiaozheng Li; Lei Wang; Xing Gao (Advanced Intelligent Systems, 2024)
Resonant actuation and multi‐degree‐of‐freedom (DoF) actuation can optimize the output matrices and greatly expand the versatility of dielectric elastomer actuators (DEAs) for practical applications. However, developing a multi‐DoF resonant DEA that benefits both from the maximized stroke outputs in resonant actuation and the versatility in multi‐DoF actuation remains a challenging task due to the slow responses of the widely adopted acrylic elastomers and the exponentially scaled complexity in the nonlinear dynamics. Herein, a multi‐DoF resonant DEA is reported by adopting four radially organized planar DE units fabricated by low‐loss silicone elastomers to output versatile programmable two‐dimensional quasi‐static and resonant trajectories. The rich nonlinear dynamics of the proposed quad‐unit DEA (QUDEA) are characterized and the critical parameters for two‐dimensional trajectory programming are uncovered through extensive modeling and experimental studies. To showcase the two‐dimensional trajectory programming capabilities of the QUDEA, demonstrations of Chinese characters writing and hummingbird flapping patterns mimicking using the proposed QUDEA are developed. The proposed QUDEA is expected to have potential in various applications such as in experimental biology, biomimetic robotics, and industrial manufacturing devices.